Air Pollution Risk Assessment: A Comparative Study of Industrial Cities of Pakistan - Faiz, Y.; Waheed, S.; Daud, M. (The Nucleus, 2016)
Currently in Pakistan there is little information regarding dose assessment for trace elements in air particulate matter (APM). US EPA health risk assessment model has been employed to calculate the elemental dose for thirty four elements quantified using instrumental neutron activation analysis (INAA) technique in APM and soil samples collected from Faisalabad and Gujranwala cities. Hazard Quotient (HQ) and Hazard Index (HI) have been assessed for Al, Ba, Co, Cr, Mn, Sb, Sr, V and Zn. Alarming elemental doses were observed as 1.91, 1.28, 1.26, 2.21 and 1.97 respectively for Al, Fe, K, Mg, and Na in suspended particulate matter (SPM) of Faisalabad. Likewise in Gujranwala the levels were 1.66, 9.84, 2.62, 1.32, 1.03 and 1.49 for Al, Ca, Fe, K, Mg and Na, respectively. For Faisalabad high HI values were evaluated for Al, Cr and Sb with respective values of 2.00, 1.01 and 1.46. Similarly, in SPM of Gujranwala the HI values for these elements were also high (1.73, 2.49E+02 and 3.94 respectively). Critically, high Cr hazard levels due to tanneries and chrome plating industries in Gujranwala city indicate alarming health hazard. Overall, Al, Cr and Sb are the current challenges to be managed.